Neurobiology of the premonitory urge in Tourette syndrome: Pathophysiology and treatment implications - Cavanna, Andrea E. (J Neuropsychiatry Clin Neurosci, 2017)
Motor and vocal tics are relatively common motor manifestations identified as the core features of Tourette syndrome. Although traditional descriptions have focused on objective phenomenological observations, such as anatomical location, number and frequency of tics, patients’ first-person accounts have consistently reported characteristic subjective correlates. These sensory phenomena are often described as a feeling of mounting inner tension or urge to move (“premonitory urge”), which is transiently relieved by tic expression. This paper reviews the existing literature on the clinical and neurobiological aspects of the premonitory urge in patients with Tourette syndrome, with focus on its pathophysiology and possible treatment implications.